Level crossing control: a novel method using sound recognition - Alim, Sabur Ajibola; Alang Md Rashid, Nahrul Khair; Rahman , Md Mozasser (Chulalongkorn University, 2013)
The level crossing (LX) or railway crossing being an intersection between a public road and a railway line, can be controlled actively or passively. Sound recognition can be used to actively control a level crossing. A system is proposed in this study for the use of sound to control a LX. This proposed system uses Mel Frequency Cepstral Coefficient (MFCC) as feature extractor, and Recurrent Neural Network (RNN) as classifier. The proposed system has shown a great potential that could be harnessed to contribute to the reduction in the loss of lives and properties at the LX.